Design and Evaluation of Clove Oil-Based Self-Emulsifying Drug Delivery Systems for Improving the Oral Bioavailability of Neratinib Maleate - Radhika Rajiv Mahajan; Punna Rao Ravi; Riya Kamlesh Marathe; Ajay Gorakh Dongare; Apoorva Vinayak Prabhu; Łukasz Szeleszczuk (MDPI AG, 2024)
Neratinib maleate (NM), a tyrosine kinase inhibitor, is used in the treatment of breast cancer. NM is orally administered at a high dose of 290 mg due to its low solubility and poor dissolution rate at pH > 3, as well as gut-wall metabolism limiting its bioavailability. Self-emulsifying drug delivery systems (SEDDSs) of NM were developed in the current study to improve its oral bioavailability. The oily vehicle (clove oil) was selected based on the solubility of NM, while the surfactant and the cosurfactant were selected based on the turbidimetric analysis. Three different sets were screened for surfactant selection in the preparation of SEDDS formulations, the first set containing Cremophor® EL alone as the surfactant, the second set containing a mixture of Cremophor® EL (surfactant) and Caproyl® PGMC (cosurfactant), and the third set containing a mixture of Cremophor® EL (surfactant) and Capmul® MCM C8 (cosurfactant). Propylene glycol was used as the cosolubilizer in the preparation of SEDDSs. A series of studies, including the construction of ternary phase diagrams to determine the zone of emulsification, thermodynamic stability studies (involving dilution studies, freeze-thaw, and heating-cooling studies), turbidimetric analysis, and physicochemical characterization studies were conducted to identify the two most stable combinations of SEDDSs. The two optimized SEDDS formulations, TP16 and TP25, consisted of clove oil (45% w/w) and propylene glycol (5% w/w) in common but differed with respect to the surfactant or surfactant mixture in the formulations. TP16 was prepared using a mixture of Cremophor® EL (surfactant) and Caproyl® PGMC (cosurfactant) in a 4:1 ratio (50% w/w), while TP25 contained only Cremophor® EL (50% w/w). The mean globule sizes were 239.8 ± 77.8 nm and 204.8 ± 2.4 nm for TP16 and TP25, respectively, with an emulsification time of <12 s for both formulations. In vitro drug dissolution studies performed at different pH conditions (3.0, 4.5, 6.8) have confirmed the increase in solubility and dissolution rate of the drug by TP16 and TP25 at all pH conditions compared to plain NM. An oral pharmacokinetic study in female Wistar rats showed that the relative bioavailability (Frel) values of TP16 and TP25 over the plain NM were 2.18 (p < 0.05) and 2.24 (p < 0.01), respectively.